2021
DOI: 10.1021/acssensors.0c02172
|View full text |Cite
|
Sign up to set email alerts
|

Microphysiological System for High-Throughput Computer Vision Measurement of Microtissue Contraction

Abstract: The ability to measure microtissue contraction in vitro can provide important information when modeling cardiac, cardiovascular, respiratory, digestive, dermal, and skeletal tissues. However, measuring tissue contraction in vitro often requires the use of high number of cells per tissue construct along with time-consuming microscopy and image analysis. Here, we present an inexpensive, versatile, high-throughput platform to measure microtissue contraction in a 96-well plate configuration using one-step batch im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…Each module ran at > 60 Hz, enabling video rate contractile force monitoring. Compared to other current video microscopy imaging techniques for 3D ECTs ( Mannhardt et al, 2016 ; Thavandiran et al, 2020 ; Gracioso Martins et al, 2021 ), our system is the first of its kind to show capability of true 96-well tissue seeding and parallel contractile force sensing, strongly aligning with the technical need and market pull for high throughput toxicity screening with 3D ECTs.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Each module ran at > 60 Hz, enabling video rate contractile force monitoring. Compared to other current video microscopy imaging techniques for 3D ECTs ( Mannhardt et al, 2016 ; Thavandiran et al, 2020 ; Gracioso Martins et al, 2021 ), our system is the first of its kind to show capability of true 96-well tissue seeding and parallel contractile force sensing, strongly aligning with the technical need and market pull for high throughput toxicity screening with 3D ECTs.…”
Section: Discussionmentioning
confidence: 89%
“…To monitor ECT contractility in an industry-standard 96 well-plate format, for example, one must currently rely on sequential imaging using robotic stage control. While some studies have demonstrated progress toward higher throughput assays ( Legant et al, 2009 ; Hansen et al, 2010 ; Spreeuwel et al, 2014 ; Polacheck and Chen, 2016 ; Mannhardt et al, 2017 ; Rocha et al, 2017 ; Martins et al, 2021 ), a bottleneck has been the field of view (FOV), and most previous efforts have relied on low-throughput serial imaging of individual wells or small groups of wells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 2 units of cavities were designed with a diameter (a2) of 6 mm for the reference and counter electrodes (Figure 1a). For 3D printing, a nozzle of 0.4 mm flexible filament was used as the material, as it is elastic and resistant to deformation [37]. The filament was printed with an extrusion For 3D printing, a nozzle of 0.4 mm flexible filament was used as the material, as it is elastic and resistant to deformation [37].…”
Section: Optimisation Of 3d-printed Electrochemical Cell and Electrod...mentioning
confidence: 99%
“…For 3D printing, a nozzle of 0.4 mm flexible filament was used as the material, as it is elastic and resistant to deformation [37]. The filament was printed with an extrusion For 3D printing, a nozzle of 0.4 mm flexible filament was used as the material, as it is elastic and resistant to deformation [37]. The filament was printed with an extrusion temperature of 240 • C and a bed temperature of 50 • C. The printing speed was optimised to 20 mms −1 with a 0.2 mm slice taking a total printing time of 1 h 57 min.…”
Section: Optimisation Of 3d-printed Electrochemical Cell and Electrod...mentioning
confidence: 99%
“…Along with the increasing efforts to fully differentiate CMs from pluripotent stem cells and, hence, derive functional engineered cardiac tissues, research is also focusing on designing and developing devices that can monitor in real-time and thus allow to progressively follow and reconstruct the whole tissue dynamics, also in response to exogenous stimuli. Technical challenges exist in the full thickness analysis but several researchers have developed advanced stimulating/sensing methods and equipment, e.g., microscopy visualization, contractility measurements, mechanical manipulation, and related high-throughput data collection that can easily combine with the engineered tissue models and, therefore, create automated, integrated platforms for robust readout ( Ramade et al, 2014 ; Pointon et al, 2017 ; Sasaki et al, 2018 ; Gracioso Martins et al, 2021 ; Ohya et al, 2021 ; Sasaki et al, 2021 ; Oguntuyo et al, 2022 ). So far, a relatively short time of a few hours or days has been dedicated to observing drug-induced alterations.…”
Section: Unmet Needs and Issues To Be Addressed For Clinical Translationmentioning
confidence: 99%